On variants and disease-causing mutations: Case studies of a SEMA4A variant identified in inherited blindness. (2nd January 2018) - Bryant, Laura; Lozynska, Olga; Han, Grace; Morgan, Jessica I. W.; Gai, Xiaowu; Maguire, Albert M.; Aleman, Tomas; Bennett, Jean
ABSTRACT: The p.R713Q variant of the semaphorin‐4a‐encoding gene, SEMA4a, has been reported to cause autosomal dominant retinitis pigmentosa. Here we show three families with retinal degeneration in which unaffected family members are either homozygous or heterozygous for the variant. The p.R713Q variant in SEMA4A is insufficient to cause either autosomal recessive or autosomal dominant retinitis pigmentosa and is unlikely to be pathogenic.